Development of a Test Instrument to Investigate Secondary School Students’ Declarative Knowledge of Quantum Optics - Bitzenbauer, Philipp (European Journal of Science and Mathematics Education, 2021)
This article reports the development and validation of a test instrument to assess secondary school students’ declarative quantum optics knowledge. With that, we respond to modern developments from physics education research: Numerous researchers propose quantum optics-based introductory courses in quantum physics, focusing on experiments with heralded photons. Our test instrument’s development is based on test development standards from the literature, and we follow a contemporary conception of validity. We present results from three studies to test various assumptions that, taken together, justify a valid test score interpretation, and we provide a psychometric characterization of the instrument. The instrument is shown to enable a reliable (α = 0.78) and valid survey of declarative knowledge of quantum optics focusing on experiments with heralded photons with three empirically separable subscales.<br
Keywords: quantum physics; test development; validation